2013
DOI: 10.1097/ajp.0b013e318266f6a5
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentration of Fentanyl During Conversion From Intravenous to Transdermal Administration to Patients With Chronic Cancer Pain

Abstract: Our study demonstrated that the dose-adjusted serum fentanyl concentrations remained relatively stable, and pain intensity and the number of rescue events remained stable during conversion. Hypoalbuminemia was strongly associated with poor absorption of transdermally administered fentanyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 14 publications
2
15
2
4
Order By: Relevance
“…It was reported previously that albumin levels and BMI interfered with the ORR to TDF . However, in our study, the ORR from MEDD to TDF did not significantly change in patients who had lower albumin and BMI.…”
Section: Discussioncontrasting
confidence: 72%
“…It was reported previously that albumin levels and BMI interfered with the ORR to TDF . However, in our study, the ORR from MEDD to TDF did not significantly change in patients who had lower albumin and BMI.…”
Section: Discussioncontrasting
confidence: 72%
“…Comparison of patients whose serum albumin levels were ≥3.0 g/dL with those whose levels were <2.5 g/dL with respect to pain control based on NRS scores showed that a higher percentage of patients responded to fentanyl in the former group. Nomura et al 16) administered transdermal fentanyl to patients with low or normal serum albumin levels and assessed the changes in serum fentanyl concentrations. They found no significant difference between the 2 groups up to 6 h after patch application.…”
Section: Discussionmentioning
confidence: 99%
“…14,15) Nomura et al 16) studied the association between the serum albumin level and serum fentanyl concentration after transdermal administration of fentanyl. They classified 18 cancer patients into the following 2 groups according to their serum albumin levels: a normal albumin group (≥3.5 g/dL) and a low albumin group (<3.5 g/dL).…”
Section: Influence Of Serum Albumin Levels During Opioid Rotation Fromentioning
confidence: 99%
“…The patients with an albumin <3.5 g dl À1 had significantly reduced doseadjusted serum fentanyl concentrations at 9-24 h after application of the patch compared to patients with an albumin >3.5 g dl À1 . The authors suggest lower absorption from the patch in patients with low plasma albumin concentrations [61]. Barrett et al showed no clinically relevant influence of albumin on fentanyl plasma concentrations in a large crosssectional study in patients using transdermal fentanyl [21].…”
Section: Patient-related Factorsmentioning
confidence: 98%
“…albumin, alpha-1-acid glycoprotein). The Variability in fentanyl pharmacokinetics effect of hypoalbuminemia was studied in two studies with a different design, both in patients using a fentanyl patch [21,61].…”
Section: Patient-related Factorsmentioning
confidence: 99%